Dimethyl fumarate ameliorates hepatic inflammation in alcohol related liver disease. (6th May 2020) - Sangineto, Moris; Grabherr, Felix; Adolph, Timon E.; Grander, Christoph; Reider, Simon; Jaschke, Nikolai; Mayr, Lisa; Schwärzler, Julian; Dallio, Marcello; Moschen, Alexander R.; Moschetta, Antonio; Sabbà, Carlo; et al.
Abstract: Background & Aims: Alcohol‐related liver disease (ALD) comprises different liver disorders which impose a health care issue. ALD and particularly alcoholic steatohepatitis, an acute inflammatory condition, cause a substantial morbidity and mortality as effective treatment options remain elusive. Inflammation in ALD is fuelled by macrophages (Kupffer cells [KCs]) which are activated by intestinal pathogen associated molecular patterns, eg lipopolysaccharide (LPS), disseminated beyond a defective intestinal barrier. We hypothesized that the immunomodulator dimethyl‐fumarate (DMF), which is approved for the treatment of human inflammatory conditions such as multiple sclerosis or psoriasis, ameliorates the course of experimental ALD. Methods: Dimethyl‐fumarate or vehicle was orally administered to wild‐type mice receiving a Lieber‐DeCarli diet containing 5% ethanol for 15 days. Liver injury, steatosis and inflammation were evaluated by histology, biochemical‐ and immunoassays. Moreover, we investigated a direct immunosuppressive effect of DMF on KCs and explored a potential impact on ethanol‐induced intestinal barrier disruption. Results: Dimethyl‐fumarate protected against ethanol‐induced hepatic injury, steatosis and inflammation in mice. Specifically, we observed reduced hepatic triglyceride and ALT accumulation, reduced hepatic expression of inflammatory cytokines ( Tnf‐α, Il‐1β, Cxcl1 ) and reduced abundance of neutrophils and macrophages in ethanol‐fed and DMF‐treated mice when compared to vehicle. DMF protected against ethanol‐induced barrier disruption and abrogated systemic LPS concentration. In addition, DMF abolished LPS‐induced cytokine responses of KCs. Conclusions: Dimethyl‐fumarate counteracts ethanol‐induced barrier dysfunction, suppresses inflammatory responses of KCs and ameliorates hepatic inflammation and steatosis, hallmarks of experimental ALD. Our data indicates that DMF treatment might be beneficial in human ALD and respective clinical trials are eagerly awaited. Abstract : In a preclinical model of alcohol‐related liver disease (ALD), the oral administration of dimethyl fumarate (DMF), a drug already used and approved for treatment of multiple sclerosis and psoriasis, revealed to be highly effective to prevent hepatic inflammation, steatosis and liver injury. In particular, DMF directly suppresses Kupffer cell activation and counteracts alcohol‐induced gut barrier disruption, preventing lipopolysaccharide (LPS) translocation.